Critical Thinking-Related Challenges to Academic Writing: A Case of Indonesian Postgraduate Students at a UK University - Udi Samanhudi; Caroline Linse (Lingua Cultura, 2019)
This research reported Indonesian students’ perspectives on challenges in writing a critical academic essay and factors causing those challenges in a university in the UK. It was a qualitative method in nature and used a semi-structured interviewing technique with open-ended questions as the main method for data collection. The results indicate four main problems the participants’ encountered in relation to critical thinking realization in their essay writing which include clarity of ideas presented, lack of critical analysis, lack of critical evaluation, and lack of precision. This research also finds three important factors causing those problems of critical thinking realization by the students in their essay writings namely lack critical awareness, lack of understanding of the critical thinking concept, and differences of academic requirements between Indonesian and British context. This research is expectedly useful as an input in the re-design of syllabi and in the improvement of writing instruction that aims to promote especially international Indonesian students’ critical thinking in university-level education, in line with properly addressing students’ needs and developing CT pedagogy in the site.